A Framework for the Surveillance of Derivatives Activities - Gutierrez, Eva (IMF Working Papers; Working Paper, 2005)
This paper proposes a framework for the surveillance of financial institutions' derivatives activities. The designed framework builds on information likely to be collected by financial market regulators for supervisory purposes, and/or information collected by market participants for the purpose of their own risk management. The framework involves four pillars: (i) analyzing quantitative information on Derivatives activities, (ii) determining the adequacy of prudential regulations and supervisory arrangements, (iii) assessing the risk mitigation infrastructure, and (iv) assessing the degree of market transparency of the derivatives activities of financial institutions.